2008
DOI: 10.1021/nn800466c
|View full text |Cite
|
Sign up to set email alerts
|

Detoxification of Gold Nanorods by Treatment with Polystyrenesulfonate

Abstract: We address an outstanding issue associated with the biocompatibility of gold nanorods (GNRs), a promising agent for biomedical imaging and theragnostics. GNRs are typically prepared in the presence of cetyltrimethylammonium bromide (CTAB), a cationic surfactant whose rigorous removal is necessary due to its cytotoxicity and membrane-compromising properties. CTABstabilized GNRs can be partially purified by treatment with polystyrenesulfonate (PSS), an anionic polyelectrolyte often used as a surrogate peptizing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
211
0
1

Year Published

2010
2010
2016
2016

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 232 publications
(217 citation statements)
references
References 47 publications
5
211
0
1
Order By: Relevance
“…The positively charged CTAB-Au NTs were coated with negatively charged sodium polystyrenesulfonate (PSS, 70 kDa) (see Experimental Section), which is commonly used as a nontoxic peptizing agent in commercial products and thus generally regarded as a safe additive. [42] After the treatment with PSS, a thin organic layer around the nanotubes was observed in TEM image ( Figure S8A), which is a direct visualization of polymer coating of the Au NTs. [43] The Zeta potential of gold nanotubes (in DI water) changed from (45±3.…”
Section: Surface Modification Of the Au Ntsmentioning
confidence: 98%
“…The positively charged CTAB-Au NTs were coated with negatively charged sodium polystyrenesulfonate (PSS, 70 kDa) (see Experimental Section), which is commonly used as a nontoxic peptizing agent in commercial products and thus generally regarded as a safe additive. [42] After the treatment with PSS, a thin organic layer around the nanotubes was observed in TEM image ( Figure S8A), which is a direct visualization of polymer coating of the Au NTs. [43] The Zeta potential of gold nanotubes (in DI water) changed from (45±3.…”
Section: Surface Modification Of the Au Ntsmentioning
confidence: 98%
“…However, when CTAB was replaced with PEG-SH, 95% of cells were viable, with the Au NRs concentration being 0.5 mM. Further works demonstrated that the replacement or overcoating of CTAB with nontoxic stabilizers of PSS, 305 PAH, 306 or copolymer poly-(diallyldimethylammonium chloride)/polystyrene sulfonic acid 307 reduced the cytotoxicity of CTAB-stabilized Au NRs. Surface charge also affects the toxicity of noble metal NPs.…”
Section: 293−296mentioning
confidence: 99%
“…These highly biocompatible ligands replace the CTAB molecules originally covering the surface of the as-synthesized NRs, which instead are known to be highly toxic. 43,44 Successful PEGylation of GNRs was verified through zeta-potential measurements of the GNRs in water before and after the ligand-exchange procedure, as described in the next section.…”
Section: Materials and Methods Materialsmentioning
confidence: 99%